Tingkat keberhasilan hidup bibit mangrove Rhizophora mucronata, R. apiculata dan Bruguiera gymnorrhiza di Delta Upang Banyuasin Sumatera Selatan - Fahmi, Khairul; Dahlan, Zulkifli; ., Sarno (Maspari Journal : Marine Science Research, 2010)
The research of the survival level of mangrove seed Rhizophora mucronata, R. apiculata and Bruguiera gymnorrhiza had been conducted during August to December 2009 in Upang Delta, Banyuasin. The objective of conducting this research was to find out the percentage of survival level of mangrove seed Rhizophora mucronata, R. apiculata, and Bruguiera gymorrhiza and to obtain some information to analyzed the level of adaptation among those three species of mangrove seed. The decision of survival level was observed based on the ability to live (%), the height of bud (cm), the number of leaf it has (sheet), and the stem illustration of observed object through sample data under such circumstances. The rate’s of presentation lives mangrove seed from threes station. First station Rhizophora mucronata 100-73,3 %, R. apiculata 100-60 % and Bruguiera gymnorrhiza 100-66,6 %. Second station, Rhizophora mucronata 100-66,6 %, R. apiculata 100-86,6 % and Bruguiera gymnorrhiza 100-73,3 %, on third station, Rhizophora mucronata 100-66,6 %, R. apiculata 100-80 % and Bruguiera gymnorrhiza 100-66,6 %. The level adaptation of but has changed comparisons of stem diameters and quantity of leaf. Keywords: Bruguiera gymnorrhiza, Mangrove, Rhizophora apiculata and R. mucronata Penelitian tingkat keberhasilan hidup bibit mangrove Rhizophora mucronata, R. apiculata dan Bruguiera gymnorrhiza telah dilaksanakan pada bulan Agustus- Desember 2009 di Delta Upang Banyuasin. Tujuan penelitian untuk mengetahui persentase keberhasilan hidup bibit mangrove Rhizophora mucronata, R. apiculata dan Bruguiera gymnorrhiza serta mengetahui dan menganalisa tingkat adaptasi ketiga bibit mangrove. Penentuan tingkat keberhasilan diamati dari persentase hidup (%), tinggi tunas (cm), jumlah daun (helai), serta diameter batang (mm). Analisis data yang digunakan secara deskriftif yaitu dengan cara memberikan gambaran terhadap objek yang diteliti melalui data sampel sebagaimana adanya. Rata-rata tingkat persentase hidup dari masing-masing bibit mangrove ketiga stasiun Rhizophora mucronata stasiun satu 100-73,3 %, R. apiculata 100-60 %, dan Bruguiera gymnorrhiza 100-66,6 %. Stasiun dua Rhizophora mucronata 100-66,6 %, R. apiculata 100-86,6 % dan Bruguiera gymnorrhiza 100-73,3 %, Pada stasiun tiga Rhizophora mucronata 100-66,6 %, R. apiculata 100-80 % dan Bruguiera gymnorrhiza 100-66,6 %. Tingkat adaptasi tinggi tunas mengalami perubahan dibandingkan diamater batang dan jumlah daun. Kata kunci : Bruguiera gymnorrhiza, Mangrove, Rhizophora apiculata a and R. mucronat.